Digest of Papers. First International Symposium on Wearable Computers 1997
DOI: 10.1109/iswc.1997.629943
|View full text |Cite
|
Sign up to set email alerts
|

Context-awareness in wearable and ubiquitous computing

Abstract: A common focus shared by researchers in mobile, ubiquitous and wearable computing is the attempt to break away from the traditional desktop computing paradigm. Computational services need to become as mobile as their users and be extended to take advantage of the constantly changing context in which they are accessed. This paper will report on work done in the Future Computing Environments Group at Georgia Tech. We describe solutions we have generated to provide a flexible context-aware infrastructure and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 3 publications
(1 reference statement)
0
35
0
1
Order By: Relevance
“…Context Type Context-Aware System Name System Description A I L T P E T Classroom 2000 [1] Capture of a classroom lecture X X X Cyberguide [1] Tour guide X X X Teleport [2] Teleporting X X X X Stick-e Documents [3,4,5] Tour guide Paging and reminders X X X X X X X X X Reactive Room [6] Intelligent control of audiovisuals X X X X GUIDE [7] Tour guide X X CyberDesk [8,9,10] Automatic integration of user services X X X Conference Assistant [11] Conference capture and tour guide X X X X X X Responsive Office [12] Office environment control X X X NETMAN [13,16] Network maintenance X X Fieldwork [17,18,22] Fieldwork data collection X X X X Augment-able Reality [19] Virtual post-it notes X X X Context Toolkit [24] In/Out Board Capture of serendipitous meetings X X X X X X X X X Active Badge [28] Call forwarding X X X X…”
mentioning
confidence: 99%
“…Context Type Context-Aware System Name System Description A I L T P E T Classroom 2000 [1] Capture of a classroom lecture X X X Cyberguide [1] Tour guide X X X Teleport [2] Teleporting X X X X Stick-e Documents [3,4,5] Tour guide Paging and reminders X X X X X X X X X Reactive Room [6] Intelligent control of audiovisuals X X X X GUIDE [7] Tour guide X X CyberDesk [8,9,10] Automatic integration of user services X X X Conference Assistant [11] Conference capture and tour guide X X X X X X Responsive Office [12] Office environment control X X X NETMAN [13,16] Network maintenance X X Fieldwork [17,18,22] Fieldwork data collection X X X X Augment-able Reality [19] Virtual post-it notes X X X Context Toolkit [24] In/Out Board Capture of serendipitous meetings X X X X X X X X X Active Badge [28] Call forwarding X X X X…”
mentioning
confidence: 99%
“…Ambient Intelligence (AmI) aims at taking the integration even one step further by realizing environments that are sensitive and responsive to the presence of people. The focus is on the users and their experience from a consumer electronics perspective, which introduces several new basic problems related to natural user interaction and context aware architectures [8] supporting human centered information, communication, service, and entertainment [2].…”
Section: Ambient Intelligencementioning
confidence: 99%
“…More recently Mitsunaga et al demonstrated the use of gaze tracking to estimate the affective state during human-robot interaction (Mitsunaga et al 2005). Efforts in the closedloop category are described in (Abowd et al 1997) and (Pentland 2004). Recent work has utilized biofeedback to understand a human's emotions, which can then be used to endow robots with "emotional intelligence".…”
Section: Related Workmentioning
confidence: 99%